2006
DOI: 10.2214/ajr.05.0998
|View full text |Cite
|
Sign up to set email alerts
|

High-Spatial-Resolution MRI of Non-Masslike Breast Lesions: Interpretation Model Based on BI-RADS MRI Descriptors

Abstract: A combination of BI-RADS MRI descriptors and clustered ring enhancement criteria is useful for the differential diagnosis of lesions showing non-masslike enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
3
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 22 publications
(39 reference statements)
10
95
3
6
Order By: Relevance
“…We also found that there was no statistical difference when considering NME internal enhancement and NME distribution in verifying malignancy. This finding is not consistent with that of a previous study by Tozaki et al (36) who found that segmental distribution, heterogeneous internal enhancement, and clustered ring enhancement were the most frequent findings in malignant NME. Some specific tumor subtypes, such as papillary carcinoma, are associated with the lowest ADC values among malignant breast tumors (37).…”
Section: Discussioncontrasting
confidence: 99%
“…We also found that there was no statistical difference when considering NME internal enhancement and NME distribution in verifying malignancy. This finding is not consistent with that of a previous study by Tozaki et al (36) who found that segmental distribution, heterogeneous internal enhancement, and clustered ring enhancement were the most frequent findings in malignant NME. Some specific tumor subtypes, such as papillary carcinoma, are associated with the lowest ADC values among malignant breast tumors (37).…”
Section: Discussioncontrasting
confidence: 99%
“…5,7,[11][12][13] Distribution was characterized as focal, linear, ductal, segmental, regional, multiple regions, and diŠuse; internal enhancement was characterized as homogeneous, heterogeneous, stippled, clumped, reticular, or clustered ring en- hancement (CRE).…”
Section: Image Interpretationmentioning
confidence: 99%
“…[6][7][8][9][10][11] In contrast, such diŠerentiation is often di‹cult with nonmass-like enhancement because there is no standardized method of interpreting non-mass-like enhancement lesions. [6][7][8]10,[12][13][14] Several studies have reported the utility of evaluating apparent diŠusion coe‹cient (ADC) values derived from diŠusion-weighted imaging (DWI) for diŠerentiating benign and malignant lesions. [15][16][17][18][19][20] DWI obtains MR signal based on the thermal diŠu-sion of water molecules (Brownian motion), and the rate of water diŠusion is expressed as the ADC value.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that the presence of this sign following washout may be useful in the diŠerential diagnosis between benign and malignant lesions. 26 In this study, the frequency of this sign was signiˆcantly diŠerent between SCD I W II and SCD III NOS ductal carcinoma (P=0.05). This may be explained by the presence of diŠuse inˆltration without the formation of large septations in ductal NOS carcinoma with a predominant scirrhous component.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 50%